Small Molecule Activation at Uranium Coordination Complexes: Control of Reactivity via Molecular Architecture (Invited Feature Article) - Meyer, Karsten; Castro-Rodriguez, Ingrid (Chemical Communications, 2006)
Electron-rich uranium coordination complexes display a pronounced reactivity toward small molecules. In this Feature article, the exciting chemistry of trivalent uranium ions coordinated to classic Werner-type ligand environments is reviewed. Three fundamentally important reactions of the [(((ArO)-Ar-R)(3)tacn)U]- system are presented that result in alkane coordination, CO/CO2 activation, and nitrogen atom-transfer chemistry.
UnivIS-Import:2015-03-09:Pub.2006.nat.dchph.laoc2.smallm
Keywords: ELECTRON-TRANSFER REACTIONS; NITROGEN-ATOM-TRANSFER; VALENT ORGANOURANIUM COMPLEXES; TRIVALENT URANIUM; CARBON-DIOXIDE; ORGANOIMIDO COMPLEXES; CRYSTAL-STRUCTURES; FUNCTIONAL-GROUPS; CHEMISTRY; AZIRIDINATION